Developing Teaching Media for the Students with Special Need - Elly Syahadati; Dewi Leni Mastuti (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
The use of media in teaching-learning process becomes a tool of communication between teachers and students. Learning style is not only centered on the teachers, but it concerns on various aspects. Those aspects are transferred into media. Teachers are not the source in learning, yet the teacher should be able to create a media. This research and development are aimed to describe the development of Bahasa and the suitability of the quality for media in teaching Bahasa. This development followed seven steps including 1) researching and collecting data, 2) planning, 3) initial product development, 4) initial trial, 5) revision, 6) field trial, 7) revision and completion of product. The research instruments were interview and questionnaire. The need analysis indicated that the subject needed real media with an interesting color. Another result showed that the media product for teaching Bahasa can be appropriately used by the children with special needs. Therefore, it can be concluded that media for teaching - learning Bahasa for deaf students in one of special needs school in Pontianak is applicable as a media in schools.